Life Estimation of HVDC Extruded Cables Subjected to Extension of Qualification Test Conditions and Comparison with Prequalification Test Conditions - Bassel Diban; Giovanni Mazzanti; Rolando Ezequiel Diaz (Energies)
The goal of this paper is to evaluate the life of HVDC extruded cables subjected to the extension of qualification test (EQT) load cycles, introduced by Cigrè Technical Brochure 852, as well as to compare the results thus obtained with those formerly obtained by the authors in the case of the prequalification test (PQT) load cycles. This goal has been achieved in the present investigation by properly modifying a previously developed procedure for the life and reliability estimation of HVDC cables—implemented in MatlabTM environment—to make it applicable to EQT load cycles in addition to PQT and type test load cycles, which are already considered in the former version of the procedure. Considering a 500 kV DC-XLPE cable as the case study, the time-varying temperature profile and electric field profile within the cable insulation are calculated. Then, the fractions of life lost and the life of the cable at five locations within the insulation thickness are evaluated by means of a proper electrothermal life model. A comparison between the electric field distributions, fractions of life lost, and cable life under EQT and PQT is carried out. In this way, important features of the EQT compared to the PQT load cycles are singled out, and eventually, a new modified extension of qualification test (MEQT) is proposed as a feasible and meaningful compromise between the pros and cons of the EQT and PQT.